Jewelry made from ancient bronze coins in the Northern Black Sea region, the Ukrainian Steppe, and the Forest-Steppe in the 6th-1st centuries BC - Orlyk, Mykhailo (Revista Arheologică, 2026)
The article is devoted to the study of the practice of using ancient bronze coins as ornaments in the material culture of the population of the Northern Black Sea region, the Ukrainian Steppe, and the Forest-Steppe in the 6th-1st centuries BC. The methodological framework is based on a combination of general scientific, historical, and numismatic methods, with a predominance of the descriptive approach, which made it possible to systematize the known finds and trace the process of their “demonetization” – the transformation from a means of payment into an element of adornment. The study analyzes 52 coins, information about which was collected from museum collections, scholarly publications, electronic catalogues, and private communications from local historians and collectors. It has been established that the problem of using ancient coins as ornaments remains insufficiently studied in historiography, despite the presence of occasional references in the works of modern researchers. A classification of “demonetized” coins is proposed based on the method of manufacture (jewelry изделия and primitively modified coins with perforations) and functional purpose (pendants, amulets, elements of clothing). Particular attention is paid to common types of bronze coins, their chronology, the geography of finds, and the specifics of their everyday use. The study expands the understanding of the non-economic functions of coins and their role in the symbolic and daily culture of ancient populations. The results of the study suggest that the process of “demonetization” of ancient bronze coins of the 6th-1st centuries BC in the Northern Black Sea region, the Ukrainian Steppe, and the Forest-Steppe was widespread and fulfilled various functions within material culture. The spatial distribution of the finds, which effectively covers most of the territory of modern Ukraine, indicates the significant spread of the practice of using coins as ornaments.
Keywords: non-monetary uses of coins; non-economic functions of coins; coins as amulets; pendant; Greek coin-set jewellery; elements of clothing decoration